THE EFFECT OF THIN CAPITALIZATION, EXECUTIVE CHARACTER AND FIRM SIZE ON TAX AVOIDANCE (Empirical Study on Property, Real Estate and Construction Companies Listed on the Indonesia Stock Exchange 2016-2020) - Muhammad Rafli Gindara; Indah Umiyati; Sri Mulyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The purpose of this study was to examine the effect of thin capitalization, executive character and firm size on tax avoidance. This study uses a population of construction and real estate companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. The sampling method used is purposive sampling. Hypothesis testing used in this study used panel data regression analysis. The research method used in this research is a quantitative research. Hypothesis testing using the E Views 9 application. The results show that the Thin Capitalization variable has a positive effect on tax avoidance, while the executive character and company size variables have no effect on tax avoidance.